Developing an improved user interface for a physically-based stream solute transport model. (July 2020) - Femeena, P.V.; Chaubey, I.; Aubeneau, A.; McMillan, S.K.; Wagner, P.D.; Fohrer, N.
Abstract: There is a growing need to address water pollution that demands advanced tools to predict the fate and transport of water quality constituents. Existing stream solute transport models use simple first-order kinetics to evaluate nutrient loss, however these ignore biochemical reactions and lack a user-friendly interface. To address this shortcoming, we integrated the One-dimensional Transport with Inflow and Storage (OTIS) model and the Enhanced Stream Water Quality Model (QUAL2E) and developed an improved interface for a physically-based solute transport model. With background algal concentration as the only calibration parameter, a generalized model was developed and evaluated. The new model performed reasonably well in predicting nutrient uptake of newly collected experimental data and published data from 32 other datasets (R 2 = 0.76, NSE = 0.47 and Percent Bias = −4.3%). Inclusion of biochemical reactions from QUAL2E improves model confidence and provides options for incorporating actual process-based data which is unfeasible in existing first-order decay-based models. Highlights: Enhanced water quality model developed by merging OTIS and QUAL2E model algorithms. Generalized model with one calibration parameter can fairly predict nutrient uptake. Improved user interface provides better modeling and data visualization options. Use of all biophysiochemical reactions improves nutrient transport representation.